N-Type doping of ε-Ga2O3 epilayers by high-temperature tin diffusion. (15th May 2021) - Bosio, Alessio; Parisini, Antonella; Lamperti, Alessio; Borelli, Carmine; Fornasini, Laura; Bosi, Matteo; Cora, Ildikò; Fogarassy, Zsolt; Pécz, Béla; Zolnai, Zsolt; Németh, Attila; Vantaggio, Salvatore; et al.
Abstract: The good control of the n -type doping is a key issue for the fabrication of efficient devices based on ε-Ga2 O3 epilayers. In this work we studied the possibility of doping the ε-Ga2 O3 thin films, epitaxially grown on c -oriented sapphire by metal-organic chemical vapor deposition, by means of a post-deposition treatment. For the first time, the n -type doping was achieved by depositing a tin-rich SnO2 film on top of the ε-Ga2 O3 layer and keeping this bi-layer system for 4 h at a temperature of 600 °C in an evacuated furnace. The diffusion of Sn atoms into the ε-Ga2 O3 film is evidenced by time-of-flight secondary-ion mass spectrometry depth profiles. Room-temperature resistivity of the order of 1 Ωcm is obtained and the electrical characterization revealed a conduction mechanism based on variable range hopping, according to the Mott's model. Graphical abstract: Image, graphical abstract